Methane pyrolysis characteristics for the practical application of hydrogen production system using permalloy plate catalyst. (15th June 2023) - Muto, Tomohiro; Asahara, Makoto; Miyasaka, Takeshi; Asato, Katsuo; Uehara, Takuma; Koshi, Mitsuo
Highlights: Experimental study on efficient methane pyrolysis condition in a medium-sized reactor. Dependence of temperature and flow rate on methane pyrolysis examined. Approximately 90 % of methane thermally decomposed using permalloy plate catalysts. Carbon formed in methane pyrolysis was fibrous and contained permalloy. Abstract: Methane pyrolysis is a hydrogen-producing method that does not emit carbon dioxide. Additionally, one of the products formed is solid carbon, which can be stored or used as a valuable byproduct to improve the economics of the process. In this study, the characteristics of the hydrogen and carbon produced by methane pyrolysis were investigated to develop a hydrogen mass-production system. Methane pyrolysis was performed in a medium-sized reactor with a capacity of approximately 40 L at a high inlet-methane flow rate using permalloy plate catalysts, which are inexpensive and more practical than supported catalysts. Notably, a maximum methane conversion of 90 % was observed with the permalloy plate catalyst. Although methane conversion increased with reactor temperature, the conversion rate decreased with an increase in flow rate. Morphological analysis results showed that when recovered at a furnace temperature of 760 °C an inlet-methane flow rate of 0.2 Nm 3 /h, the carbon was agglomerated, with a mixture of spherical and fibrous carbon. The compositional analysis results demonstrated that the generated carbon retained the metallic components of the catalyst, which were considered to have been removed from the catalyst surface. In addition, the amount of hydrogen generated and the efficiency of methane pyrolysis increased significantly with the furnace temperature. Furthermore, this study confirmed the optimal temperature and flow conditions for efficient methane pyrolysis. We deduced that the thermal decomposition of methane, including the gas-phase reaction, was more efficient at relatively high temperatures (above 800 °C), while designing inlet-methane flow rates specifically for each system could generate hydrogen at high efficiencies. Thus, the results of this study can also be used as an indicator to determine the optimal conditions of methane pyrolysis.